Pelaksanaan Prinsip Business Judgment Rule (BJR) Oleh Direksi Pada PT. Tirta Amarta Bottling Company - Noer, Muhammad Halil Gilbran; Handoko, Widhi (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2023)
AbstractThe laws and regulations divide the form of the company into two, namely legal entities and non-legal entities. Limited Liability Company as a company with legal entity is a capital alliance and was established based on agreement and the existence of a company organ. Board of Directors has the duties and functions to carry out the